Fixed-Term Contracts and the Duration Distribution of Unemployment - Maia Güell (Institute for the Study of Labor (IZA), 2003)
In the mid-1980s, many European countries introduced fixed-term contracts. Since then their labor markets have become more dynamic. This paper studies the possible implications of such reforms for the duration distribution of unemployment. I estimate a parametric duration model using cross-sectional data drawn from the Spanish Labor Force Survey from 1980 to 1994 to analyze the probability of leaving unemployment before and after the introduction of fixed-term contracts. I find that the difference in the probability of leaving unemployment between the short and long term unemployed increased after this reform. Semi-parametric estimation of the model also shows that for long spells, the probability of leaving unemployment decreased between the mid-1980s and the early 1990s.
Keywords: C41; J63; J64; 330; cross-sectional data; duration model; turnover; Befristeter Arbeitsvertrag; Arbeitslosigkeit; Dauer; Spanien